2016
DOI: 10.1007/s00253-016-7518-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biological phosphorus removal with different carbon sources

Abstract: Enhanced biological phosphorus removal (EBPR) process is one of the most economical and sustainable methods for phosphorus removal from wastewater. However, the performance of EBPR can be affected by available carbon sources types in the wastewater that may induce different functional microbial communities in the process. Glycogen accumulating organisms (GAOs) and polyphosphate accumulating organisms (PAOs) are commonly found by coexisting in the EBPR process. Predominance of GAO population may lead to EBPR fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(30 citation statements)
references
References 66 publications
0
30
0
Order By: Relevance
“…The relative proportions of VFAs in the UFAT overflow were also more consistent than those measured in the PE. Previous studies indicated that VFA uptake rates of PAOs were similar using either acetate or propionate as carbon sources, while GAOs seem to have different preferences (Shen & Zhou 2016;Dai et al 2007;Oehmen et al 2006). VFA feeding strategies such as switching use of acetate/propionate (Lu et al, 2006), dosing VFA slowly and continuously (Tu and Schuler, 2013), feeding a combination of acetate and propionate (López-Vá zquez et al, 2009), and propionate-feeding under different C/P ratios (Broughton et al, 2008) were found to enrich lab-scale reactors with Accumulibacter, while excluding GAOs.…”
Section: Impacts Of Vfa Compositionmentioning
confidence: 95%
“…The relative proportions of VFAs in the UFAT overflow were also more consistent than those measured in the PE. Previous studies indicated that VFA uptake rates of PAOs were similar using either acetate or propionate as carbon sources, while GAOs seem to have different preferences (Shen & Zhou 2016;Dai et al 2007;Oehmen et al 2006). VFA feeding strategies such as switching use of acetate/propionate (Lu et al, 2006), dosing VFA slowly and continuously (Tu and Schuler, 2013), feeding a combination of acetate and propionate (López-Vá zquez et al, 2009), and propionate-feeding under different C/P ratios (Broughton et al, 2008) were found to enrich lab-scale reactors with Accumulibacter, while excluding GAOs.…”
Section: Impacts Of Vfa Compositionmentioning
confidence: 95%
“…Normally, Pi is removed from wastewaters by chemical precipitation, which is an expensive process [78]. Biological Pi removal is an alternative to chemical treatments in which bacteria accumulate excess Pi as polyphosphate (polyP) [79,80]. The bacteria can then be retained as sludge, which can be separated from the wastewater, which now has a much reduced phosphorous concentration.…”
Section: The Response To High Levels Of Extracellular Pimentioning
confidence: 99%
“…Beyond specific yield, should algal fermentation be integrated into a WRRF, carboxylate speciation is equally, if not more, important. For example, research strongly supports that VFAs (specifically propionic acid) can enhance EBPR (Carvalheira et al, 2014;Shen and Zhou, 2016). Moreover, should polyhydroxyalkanoates production become a focus, a diverse array of carboxylic acids will result in a better-quality polymer (Anderson and Dawes, 1990;Dias et al, 2006).…”
Section: Resultsmentioning
confidence: 99%